PERANCANGAN APLIKASI TRACER STUDY ALUMNI JURUSAN ADMINISTRASI BISNIS POLITEKNIK NEGERI BANJARMASIN BERBASIS WEB - Tajudin Noor; Said Muhamad; Rahma Indera (POSITIF : Jurnal Sistem dan Teknologi Informasi, 2016)
Graduates is one of the important components within an educational institution in addition to students, faculty and stakeholders. Graduates is an educational product used  by  public. So it can be said that the Graduates is one of the parameters  to determine the success or failure of educational instituusi.To find the career increment and Graduate’s life, Business Administration Program Study State Polytechnics of Banjarmasin have a unit. Some way to gathering information about  graduates  with the phone and  fill in  form directly by graduates. Based on existing mechanisms, still have some weaknesses, they are not all of graduates are willing to be contacted by the officers, and not all graduates can fill in a form.The  purpose of this application is facilitate  the  collect  of  information  on  the graduates website for the application form so that most of graduates can access it more easily. This application was made with Waterfall development method.